Determination of electricity prices for industrial consumers - Дорошенко, Олександр Іванович (Technology audit and production reserves, 2016)
Based on the physics of normal electric power transmission, the paper proposes a new, science-based approach to determining the wholesale and retail electricity prices for industrial and equated consumers, which is accounted the effect of schemes for their power from the power system and reactive load on the economy of electric power transmission process. Given the fact that pricing in the electricity system is the basic system calculation that determines the economics of its operation, it is proposed to conduct three levels: selling price; wholesale price; retail price. In the article is scientifically based the principles for determining the selling, wholesale and retail electricity prices, which takes into account the physics of the impact of voltage electricity network on pricing (as a potential form of electricity) that feeds consumer, its active loss and bandwidth depending on the concept consumer connection to electric networks of electric power transmission organizations (as the basis of the methodology for determining wholesale prices) and reactive power load for specific electricity consumer (as the basis of the methodology for determining the retail price) for the consumed electricity in the current period.